Workshop Pengembangan Kegiatan Pembelajaran Berbasis Keterampilan Proses Sains pada Calon Guru Paud Universitas Mataram - Sriwarthini, Ni Luh Putu Nina; Rachmayani, Ika; Wardani, Ketut Sri Kusuma; Wahab, Aulia Dwi Amalina; Sativa, Filsa Era (LPPM Universitas Flores, 2022)
PAUD students as an Early Childhood Education teachers candidate are required to provide innovations in learning approaches, methods, and media using concrete objects nor teaching aids, so they can conduct innovative learning. In fact, from the results of an initial survey that conducted on 6th semester PAUD students using google form, it was found that both studets and teachers are struggling to be able to design a proper science learning. Based on these findings, the PKM team conducts training and mentoring for PAUD teachers candidate to help them facing obstacles in developing learning activities that are able to improve science process skills that suitable for early childhood development. This activity will provide insight and knowledge to students to be able to sort out and design science learning activities for early childhood. The results obtained from this activity were increasing student skills in designing learning activities based on science process skills